2017
DOI: 10.1166/asl.2017.10480
|View full text |Cite
|
Sign up to set email alerts
|

Political Connection, Board Characteristics and Environmental Disclosure in Nigeria

Abstract: The poor environmental performance and by extension low level of environmental disclosure evident in the annual reports of quoted Nigerian companies have aroused stakeholders concern about the condition of the environment. The main objective of this study is to x-ray the relationship between political connection, board characteristics and environmental disclosure. The quantitative approach will be adopted using data from the annual reports of the sampled companies. The theoretical framework is built on the leg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
14
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 32 publications
5
14
2
1
Order By: Relevance
“…Therefore, we, reject H5. The results contradict the earlier finding of Osazuwa et al (2016) in Nigeria and (Ntim & Osei, 2011) from South Africa. Table 11 shows coefficients and significance of environmental committee in all the models for South Africa and Nigeria.…”
Section: Multivariate Analysiscontrasting
confidence: 99%
See 2 more Smart Citations
“…Therefore, we, reject H5. The results contradict the earlier finding of Osazuwa et al (2016) in Nigeria and (Ntim & Osei, 2011) from South Africa. Table 11 shows coefficients and significance of environmental committee in all the models for South Africa and Nigeria.…”
Section: Multivariate Analysiscontrasting
confidence: 99%
“…However, the results also indicate that both board size and Audit firm size (Big4) in both countries M7 have a positive and statistically significant relation (p=0.0034, p=0.0315) and (p=0.0284, p=0.0428) respectively.Based on the evidence, board size and firm audit size associate more to the extent of environmental disclosure among listed companies in South Africa and less in Nigeria. The results agree with the findings of (Akbas, 2016;Haniffa & Cooke, 2005;Jizi et al, 2013;Ntim & Osei, 2011;Osazuwa et al, 2016) that board size influences the extent of environmental disclosure. The finding agrees with agency theory (John & Senbet, 1998) that having a large board comprising a diversity of expertise (Sun, Salama, Hussainey, & Habbash, 2010) encourages more disclosure.…”
Section: Multivariate Analysissupporting
confidence: 91%
See 1 more Smart Citation
“…Equally, the debt to equity ratio (Kılıç and Kuzey 2018 ) and the profitability of the company (Brooks and Oikonomou 2018 ) influence the company in disclosing environmental accounting information to the stakeholders. Board characteristics cannot be underscored when it comes to internal factors that influence environmental accounting information disclosure (Osazuwa et al 2016 ; Passetti et al 2018 ). Board characteristics that are identified as determinants of environmental information disclosure in the mining companies are the size of the board (Vogt et al 2017 ; Osazuwa et al 2016 ; García‐Sánchez and Martínez‐Ferrero 2018 ), the proportion of independent directors (García‐Sánchez and Martínez‐Ferrero 2018 ; Cucari et al 2018 ), establishment of professional committees (Osazuwa et al 2016 ), the female representation of the board (Elmagrhi et al 2019 ) CEO duality (Cucari et al 2018 ), and age range of board members (Fernandes et al 2019 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…By analysing the size of the board of directors, for instance, several studies found a positive influence of its large size on the level of environmental disclosure (Siregar and Bachtiar 2010;Htay et al 2012;Rao et al 2012;Andrikopoulos and Kriklani 2013;Raman and Bukair 2013;Jizi et al 2014;Shamil et al 2014;Khlif et al 2015;Osazuwa et al 2016;Trireksani and Djajadikerta 2016). By analysing the board composition, other studies find that the firms' engagement in sustainability reporting, as well as the quantity and quality of disclosed information, is positively influenced by the presence of independent directors and of a dual leadership structure (Chau and Gray 2010;Zhang 2012;Jizi et al 2014;Shamil et al 2014;Liao et al 2015;Eberhardt-Toth 2017).…”
Section: Literature Reviewmentioning
confidence: 99%